Disability And State: A Study On Government Policy In India (Journal of Namibian Studies : History Politics Culture, 2023)
The Constitution of India ensures equality, freedom, justice and dignity of all individuals and implicitly mandates an inclusive society for all including persons with disabilities. In the recent years, there have been vast and positive changes in the perception of the society towards persons with disabilities. As per the Census 2011, the differently abled population in India is 26.8 million. There has been a marginal increase in the differently-abled population in India, with the figure rising from 21.9 million in 2001 to 26.8 million over the period of 10 years. In last few decades the awareness of disability increase in our society, several factors were involved in the rise of disability awareness. Government of India takes policy and numbers of legislation for disable people provide them equal status and respect in our society.